Digital maturity in microtextile enterprises in the Ambato canton: Current status and management challenges (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2026)
The purpose of this study was to evaluate the digital maturity of microenterprises in the textile sector of the Ambato canton, in order to understand the level of technological adoption achieved and the main limitations hindering progress toward more digital management models. This work arose from the need to understand how small local production units are facing the challenges of digital transformation in a context marked by competitiveness and rapid technological evolution. The research was conducted using a quantitative and descriptive approach, applying a structured survey to 171 textile microenterprises. The questionnaire, with a Likert scale, addressed three dimensions: D1. Current use of technologies in the company, D2. Challenges in the adoption of digital technologies, and D3. Benefits and perspectives of digital transformation. The results showed that more than 97% of the companies are at “very low” or “low” levels of digitalization, characterized by the limited use of technological tools and a dependence on social media for product promotion and sales. Among the main barriers identified are: lack of capital, limited training in digital skills, and absence of specialized technical support—factors that hinder the full integration of technology into production processes. Even so, a positive attitude toward innovation and a growing interest in incorporating emerging technologies were observed. In conclusion, the study highlights the urgent need to strengthen digital capabilities and promote public policies that support the sustainable technological transformation of the sector.
Keywords: digitization; technological tools; digital maturity; textile micro-enterprises